2013
DOI: 10.1097/scs.0b013e31826468f5
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Removal Rates for Mandibular Angle Fractures

Abstract: Overall, removal rates between Champy line and 8-hole strut plates are not different in treating mandibular angle fractures, although the 8-hole strut plate has a lower rate of loose hardware-related plate removal compared with the Champy line plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…There were 9 RCTs [ 9 , 10 , 14 – 20 ] and 4 CCTs (3 retrospective studies [ 21 23 ] and 1 prospective study [ 8 ]) in this meta-analysis, consisting of 593 participants (339 in 3D miniplate group and 254 in standard miniplate group). The characteristics of the 13 included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 9 RCTs [ 9 , 10 , 14 – 20 ] and 4 CCTs (3 retrospective studies [ 21 23 ] and 1 prospective study [ 8 ]) in this meta-analysis, consisting of 593 participants (339 in 3D miniplate group and 254 in standard miniplate group). The characteristics of the 13 included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the Champy technique, the standard miniplate needs to be placed on the external oblique line, which leads to the proximity to incision, whereas the 3D miniplate could easily avoid this situation as it is covered by the masseter along the buccal cortex, well away from the incision [ 15 , 21 ], and this might be the reason for differences between the two miniplates in the incidence of wound dehiscence. The pooled results integrating 6 studies in this meta-analysis indicated a dramatic reduction (64%) in the incidence of wound dehiscence using 3D miniplate than the standard, however, without significant difference ( P = 0.07), which might be due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…9,19,20 Although the 3D strut plate is a relatively recent development in the treatment of mandibular angle fractures, the current literature documents successful clinical and biomechanical outcomes. 1,5,17,[20][21][22][23][24] A study done using sheep mandibles and a class III cantilever model found that the degree of displacement and gap formation of the 3D strut plate is comparable to that of a reconstruction Plate. 13 The design of the strut plates confers a significant advantage over single plate and two-plate fixation methods on the lateral surface of the mandible.…”
Section: Discussionmentioning
confidence: 93%
“…The primary reason for plate removal in that study was attributed to loose fixation screws and Plates. 21 Only 10 patients (4.5%) developed postoperative infections and required surgical incision and drainage with removal of the fixation plates due to the infection. The angle fracture in all of these cases was displaced more than 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies as to the removal of the plates after healing of the mandibular fractures. [ 2 3 32 33 34 35 36 37 38 39 ] Most of these studies have concluded that routine removal of the plates is not necessary because complication rates are relatively low. These studies have suggested the removal of symptomatic plates only.…”
Section: Discussionmentioning
confidence: 99%